CCA Security for Self-Updatable Encryption: Protecting Cloud Data When Clients Read/Write Ciphertexts. (12th December 2018) - Lee, Kwangsu; Lee, Dong Hoon; Park, Jong Hwan; Yung, Moti
Abstract: Self-updatable encryption (SUE) is a new kind of public-key encryption, motivated by cloud computing, which enables anyone (i.e. cloud server with no access to private keys) to update a past ciphertext to a future ciphertext by using a public key. The main applications of SUE are revocable-storage attribute-based encryption (RS-ABE) that provides an efficient and secure access control to encrypted data stored in cloud storage. In this setting, there is a new threat such that a revoked user still can access past ciphertexts given to him by a storage server. RS-ABE solves this problem by combining user revocation and ciphertext updating functionalities. We propose the first SUE and RS-ABE schemes secure against a relevant form of chosen-ciphertext security (CCA). Due to the fact that some ciphertexts are easily derived from others, we employ a different notion of CCA that avoids easy challenge related messages. Specifically, we define "time extended challenge" CCA security for SUE which excludes ciphertexts that are easily derived from the challenge (over time periods) from being queried on. We then propose an efficient SUE scheme with such CCA security, and we also present an RS-ABE scheme with this CCA security.